IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP LARANGAN PENGGUNAAN JARING TRAWL BERDASARKAN PERATURAN PERUNDANG-UNDANGAN PEMERINTAH TIMOR-LESTE NOMOR 6 TAHUN 2004 - Salomão de Araujo Guereiro; Francisca Romana Harjiyatni; Sunarya Raharja (Kajian Hasil Penelitian Hukum, 2018)
The aim of this research are to find out how to implementation of government politicies for management of marine environment. Related activities of fishermen to use the type of trawling nets: and also to know the effectiveness of supervision on the damage of marine environment due to taking of the fish use of trawling nets  by fishermen: This research are using by the normative met head and this research also has supported by empirical, that obtained in the field.Resource person in this research are: Head of Conservation Lino de Jesus Martins, Head of IGPRP Lucas Fernandes, Head of Director National Board Orlando H Kalis, Head of investigation section of fisheries board Tomas G. R. de Sousa, Head of Biqueli village Daniel Martins and Head of Community shop Filipe Pereira while respondent in this research are 50 people fishermen in Biqueli village.            So the result of this research that quantitative analysed based on the quality in a system form and draw the conclusion that in accordance with existing legal issues. The results of this research just show that all this time of the fishermen often use the trawl nets before the socialization of the ministry of fisheries against many fishermen use the trawl nets in the their daily livelihood.            After the government socialization there were fishermen with a number of presentation rose to 60 percent, who understand the rules for implementing government policies related arrest fish with use the trawl nets, while 4 percent fishermen have not obtained information sauces details about ban on the implementation of government policies against the use existing of trawl nets, so threat the observation research in the field show the many fishermen currently no longer operate in the activities to catch the fish with trawl nets, because the government has anticipated with preventive steps through information sharing in the form of socialization, training, counselling and posting posters about the ban on fishing in the area of management marine environment